PENGARUH PEMBINAAN TERHADAP KEDISIPLINAN TARUNA DI SEKOLAH TINGGI PERIKANAN JURUSAN PENYULUHAN PERIKANAN BOGOR - Adi Apriyadi; Beddy Iriawan Maksudi; Denny Hernawan (Jurnal Governansi, 2017)
The purpose of this research are : (1) to know how the coaching of cadets in STP Bogor Fishery Counseling Department, (2) to know how the influence of coaching on cadet discipline in Fishery High School Bogor, Department of Fisheries Counseling, and (3) to know what factors are influence the coaching process in improving cadet discipline. The research method used by researcher is descriptive research method. The sampling technique using in this research is the formula of Taro Yamane and Slovin with the number of pupolation as many as 76 people cadets.Result of analysis of correlation coefficient test showed that with sample number of 76 people and trust level of 0.05 or 95% coaching variable (X) and discipline variable (Y) have correlation value of 0,742 and significance level equal to 0.001 <ɑ 0.05 or 95% of confidence level. This mean that the value asserts that the coaching variables have a strong and significant relationship, so the hypothesis proposed was accepted. From many indicators that can affect the level of cadet discipline in the Fishery High School of Bogor, Department of Fisheries Counseling one of them is coaching factor. Coaching is instrumental in determining the cadets' divinity, because the Coach is used as an example and role model by the cadets. The coach should not expect the discipline as good as it is if his coaches can not exemplify discipline.Good discipline reflects the magnitude of a person's sense of responsibility for the tasks assigned to him. This encourages the passion of learning and follow all activities that available and can realize the goal of the Fishery High School of Bogor, Department of Fisheries Counseling. The amount of determination coefficient between the variables of coaching on cadet discipline in Fishery High School Department of Fisheries Counseling is equal to 51.1%, while the rest is equal to 48.9%Keywords: Coaching, Cadet Discipline